2022
DOI: 10.3390/separations9080209
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epigallocatechin-3-Gallate (EGCG) from Green Tea Using Mass Spectrometry

Abstract: In an era where humanity is reinstating its lost hope and expectation on natural products, green tea occupies quite a position for what it has proven to be, in its endeavors for human welfare and health. Epigallocatechin-3-gallate (EGCG) is the key to the vast biological activities of green tea. Green tea is no longer in the backdrop; it has emerged as the most viral, trending bioactive molecule when it comes to health benefits for human beings. This review focuses on the use of various analytical techniques f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 168 publications
0
5
0
Order By: Relevance
“…Comparing to the results of the previous studies, EGCG cream and combine cream in our study had greater effect on sebum reduction. It may be caused by the effects of the following factors: (1) The green tea compound contains several polyphenol compounds with approximately 40%–60% EGCG 21 . In fact, EGCG is the most potent polyphenol derivative along with the anti‐androgen activity which cannot be found in some derivatives 7,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing to the results of the previous studies, EGCG cream and combine cream in our study had greater effect on sebum reduction. It may be caused by the effects of the following factors: (1) The green tea compound contains several polyphenol compounds with approximately 40%–60% EGCG 21 . In fact, EGCG is the most potent polyphenol derivative along with the anti‐androgen activity which cannot be found in some derivatives 7,21 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be caused by the effects of the following factors: (1) The green tea compound contains several polyphenol compounds with approximately 40%–60% EGCG 21 . In fact, EGCG is the most potent polyphenol derivative along with the anti‐androgen activity which cannot be found in some derivatives 7,21 . From previous both in vitro and in vivo studies, it was found that the concentration of green tea or EGCG potentially tended to affect its anti‐sebum efficacy 6,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, conventional methods for the quantitative determination of EGCG use high-(or ultra-high-) performance liquid chromatography alone or in combination with mass spectrometry [20][21][22][23]. However, although sample types may be limited, a simple and convenient method using a spectrophotometer is available without expensive analytical devices [17].…”
Section: Applicability Of the Spectrophotometric Assay For Egcg Level...mentioning
confidence: 99%
“…Catechins are the most abundant polyphenols in tea which account for 70-80% of the total polyphenols. There are four types of catechins that are most dominant in tea, namely (-)-epicatechin (EC), (-)-epigallocatechin (EGC), (-)-epicatechin-3-O-gallate (ECG), and (-)-epigallocatechin -3-O-gallate (EGCG), where of the four types of catechins, the concentration of EGCG dominates as much as 50-80% of the total catechins (Koch et al, 2018;Sivanesan et al, 2022). Therefore, further studies are needed to identify the total catechins in the stem bark of S. quadri da so that further comparisons can be made.…”
Section: Determination Of (+)-Catechinmentioning
confidence: 99%